Analysis of Cooling a Printed 3D Mold Using a Casting and Solidification Simulation of a CuSn20 Bronze Bell Casting - M. Nadolski; Ł. Bernat; D. Cekus; P. Kwiatoń; A. Pietrzak (Archives of Metallurgy and Materials)
The work done in this study is a preliminary investigation into the possibility of modelling the filling and solidification process of castings in molds made with the additive method. The work originated from an experiment to produce a bronze casting with a high tin content in an additive mold. The mold filling and solidification simulation was carried out in the MAGMASO FT program, and the lambda thermal conductivity coefficient used in the program’s material database was corrected based on the actual temperature values of the printed form. The results were compared with the modeling results for the physical properties of furan molds based on the program database. The microstructure of the castings obtained in the compared forms was assessed.